International economics - Salvatore, Dominick (Upper Saddle River, N.J. : Prentice Hall, 1999)
International trade theory. International trade policy. The balance of payments and exchange rates. Open-economy macroeconomics and the international monetary system.
Keywords: Economics; International economic relations